Glass Bracelets with Inner Metal Wire from Turov Land: preliminary publication - Ekaterina A. Kukharava (Археология евразийских степей)
The study of glass bracelets from Turov, Pinsk and Kletsk revealed artefacts with a specific technological characteristic - the presence of metal wire inside the glass hoop. These items were placed in a separate group, their morphological and technological study and analysis of the chemical composition of glass and wire were carried out. It was established that the studied characteristic is found among twisted, smooth rounded and fluted bracelets made mainly of transparent and translucent glass of turquoise colour. The analyzed sample is represented by three chemical types of glass: potassium-lead-silica, lead-silica, and sodium-lead-silica, which allowed us to link the origin of the bracelets with specific technological characteristics to ancient Russian and probably Byzantine production.